1988
DOI: 10.1016/0735-1097(88)91519-7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction and normal coronary arteriography: A 10 year clinical and risk analysis of 74 patients

Abstract: Myocardial infarction with normal coronary arteries was identified in 74 patients with a mean age of 43 years (range 19 to 66). A mean follow-up period of 10.5 years after documented myocardial infarction and 8.6 years after cardiac catheterization was obtained. The survival rate was 85% (n = 63). There were no statistical differences in age or clinical risk factor prevalence between survivors and nonsurvivors. Moderate (55%) to severe (27%) left ventricular impairment was more common in nonsurvivors. Nine of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
2
8

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 24 publications
7
58
2
8
Order By: Relevance
“…Second, there appears to be an ethnic predisposition to coronary spasm in patients with a recent myocardial infarct, 14 particularly among Japanese patients. 15 Fukai et al 16 from Japan reported an 81% prevalence of inducible spasm in patients with MINOCA, whereas studies from Europe [17][18][19][20] and the United States 21,22 have a pooled prevalence of only 14%. Interestingly, other Asian-based studies 23,24 also report a high prevalence of inducible spasm (Table 3).…”
Section: Coronary Spasmmentioning
confidence: 99%
“…Second, there appears to be an ethnic predisposition to coronary spasm in patients with a recent myocardial infarct, 14 particularly among Japanese patients. 15 Fukai et al 16 from Japan reported an 81% prevalence of inducible spasm in patients with MINOCA, whereas studies from Europe [17][18][19][20] and the United States 21,22 have a pooled prevalence of only 14%. Interestingly, other Asian-based studies 23,24 also report a high prevalence of inducible spasm (Table 3).…”
Section: Coronary Spasmmentioning
confidence: 99%
“…Various mechanisms have been hypothesized, such as coronary spasm, and acquired or inherited coagulation disorders (9,33). Myocarditis can also mimic ACS with angiographically normal coronary arteries; one-year mortality rates as high as 15% to 20% have been reported in patients developing acute (nonfulminant) myocarditis (5-7).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of MI with normal to near-normal coronary arteries in the general population varies between 1 and 12% depending on the definition of "normal coronary vessels" [7][8][9][10]. This pattern is more commonly seen in younger individuals.…”
Section: Introductionmentioning
confidence: 99%